2022
DOI: 10.1126/scisignal.abn6875
|View full text |Cite
|
Sign up to set email alerts
|

Protein tyrosine phosphatase 1B regulates miR-208b-argonaute 2 association and thyroid hormone responsiveness in cardiac hypertrophy

Abstract: Increased production of reactive oxygen species plays an essential role in the pathogenesis of several diseases, including cardiac hypertrophy. In our search to identify redox-sensitive targets that contribute to redox signaling, we found that protein tyrosine phosphatase 1B (PTP1B) was reversibly oxidized and inactivated in hearts undergoing hypertrophy. Cardiomyocyte-specific deletion of PTP1B in mice (PTP1B cKO mice) caused a hypertrophic phenotype that was exacerbated by pressure overload. Furthermore, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 69 publications
(124 reference statements)
0
3
0
Order By: Relevance
“…While our results herein suggest a protective cardiac effect in response to deletion of PTP1B in the heart, one recent paper suggests a different role; Coulis et al suggest that CM-specific deletion of PTP1B in mice may be pathological, inducing a hypertrophic phenotype that is exacerbated by pressure overload 103 . Specifically, they claim that argonaute 2 (AGO2), a critical component of the RNA-induced silencing complex, is inactivated in response to CM-specific deletion of PTP1B, thereby preventing miR-208bmediated inhibition mediator complex subunit 13 (MED13) and leading to thyroid hormone-mediated pathological cardiac hypertrophy.…”
Section: Discussioncontrasting
confidence: 70%
“…While our results herein suggest a protective cardiac effect in response to deletion of PTP1B in the heart, one recent paper suggests a different role; Coulis et al suggest that CM-specific deletion of PTP1B in mice may be pathological, inducing a hypertrophic phenotype that is exacerbated by pressure overload 103 . Specifically, they claim that argonaute 2 (AGO2), a critical component of the RNA-induced silencing complex, is inactivated in response to CM-specific deletion of PTP1B, thereby preventing miR-208bmediated inhibition mediator complex subunit 13 (MED13) and leading to thyroid hormone-mediated pathological cardiac hypertrophy.…”
Section: Discussioncontrasting
confidence: 70%
“…Except for miR-206, the other six myomiRs, miR-1, miR-133a, miR-133b, miR-208a, miR-208b, and miR-499, can be expressed in cardiac muscles. Moreover, multiple studies have demonstrated that these myomiRs are involved in the development of different types of heart diseases, including dilated cardiomyopathy ( 33 ), coronary artery disease ( 34 ), cardiac hypertrophy ( 35 , 36 ), and myocardial fibrosis ( 37 , 38 ). Although miR-208a and miR-208b were not remarkably higher in the sera of cardiac involvement patients, we believe this may suggest that miR-1, miR-133a, miR-133b, and miR-499 are more sensitive to cardiac involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple classical PTP genes harbour transcriptional units on the complementary strand that are annotated as antisense, microRNA, lncRNA or circRNA gene, and that are impacting, at least, on transcripts originating from their host gene (Mandemakers et al, 2013;Xing et al, 2014;Abuhatzira et al, 2015;Yao et al, 2015;Zhou et al, 2016;Han et al, 2019;John et al, 2019;Wei et al, 2019;Dai et al, 2020;Ma et al, 2020;Shi et al, 2020;Grad et al, 2022;Wu et al, 2022). Intriguingly, also in return PTPs may have bearing for microRNAs themselves, as was recently noted for PTP1B's impact on the phosphorylation level of the argonaute two protein, and thus its association with miRNAs (Coulis et al, 2022). Obviously, all these levels of (reciprocal) interactions provide a real challenge to map genotype-phenotype effects for the overwhelming stream of gene variants now that the whole-genome sequencing locks have opened.…”
Section: Genetic Investigationsmentioning
confidence: 91%